Calculation of Some Integrals Arising in Heat Transfer in Grinding. (22nd August 2010) - Santander, J. L. G.; Castañeda Porras, P.; Ratis, Yu. L.; Isidro, J. M.; Fernández de Córdoba, P.
Abstract : We calculate some integrals involved in the temperature field evaluation of a workpiece during the grinding process. For the case of dry continuous grinding, this calculation allows a faster computation of the temperature field on surface and inside the workpiece.